An NMR study on the interaction of Escherichia coli DinI with RecA–ssDNA complexes - Yoshimasu, Masatoshi (Oxford University Press, 2003)
The SOS response, a set of cellular phenomena exhibited by eubacteria, is initiated by various causes that include DNA damage-induced replication arrest, and is positively regulated by the co- protease activity of RecA. Escherichia coli DinI, a LexA-regulated SOS gene product, shuts off the initiation of the SOS response when overexpressed in vivo. Biochemical and genetic studies indicated that DinI physically interacts with RecA to inhibit its co-protease activity. Using nuclear magnetic resonance (NMR) spectroscopy, we show that DinI tightly binds to the central region of RecA (between the N- and C-terminal domains) and that this interaction is enhanced upon the oligomerisation of RecA. On the other hand, DinI did not inhibit the interaction between 4mer single-stranded (ss)DNA and RecA– ATPγS, but had a slight effect on the structure of ssDNA–RecA–ATPγS complexes involving 8mer and 12mer ssDNA. We hypothesise that prevention of repressor binding to the intermolecular cleft region of RecA protomers by DinI, with the possibility of a slight conformational change induced in the DinI-bound ssDNA–RecA–ATPγS complex, together function to inhibit the co-protease activity of RecA.